1989
DOI: 10.1037/0033-2909.106.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Frustration-aggression hypothesis: Examination and reformulation.

Abstract: Examines the Dollard et al. (1939) frustration-aggression hypothesis. The original formulation's main proposition is limited to interference with an expected attainment of a desired goal on hostile (emotional) aggression. Although some studies have yielded negative results, others support the core proposition. Frustrations can create aggressive inclinations even when they are not arbitrary or aimed at the subject personally. Interpretations and attributions can be understood partly in terms of the original ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

104
1,173
8
74

Year Published

1996
1996
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,736 publications
(1,418 citation statements)
references
References 98 publications
104
1,173
8
74
Order By: Relevance
“…Consistent with Berkowitz's (1989Berkowitz's ( , 1990Berkowitz's ( , 1993) model of aggression, provocation-induced negative affect was associated with increased displaced aggression for participants induced to ruminate but not for those who were distracted or were induced to think positively. Other correlational evidence suggested that within the rumination condition, the stronger the provocation-induced negative affect, the more negative was participants' reaction to the trigger.…”
Section: Discussionsupporting
confidence: 66%
“…Consistent with Berkowitz's (1989Berkowitz's ( , 1990Berkowitz's ( , 1993) model of aggression, provocation-induced negative affect was associated with increased displaced aggression for participants induced to ruminate but not for those who were distracted or were induced to think positively. Other correlational evidence suggested that within the rumination condition, the stronger the provocation-induced negative affect, the more negative was participants' reaction to the trigger.…”
Section: Discussionsupporting
confidence: 66%
“…It is associated with the frustration theory of aggression (Berkowitz 1989) and is accompanied by an activation of the autonomous system (Hubbard et al 2002). In contrast, proactive aggression is considered a non-provoked behavior that is motivated by the desire for personal gains or the domination of others (Vitaro and Brendgen 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike proactive or instrumental aggression, reactive aggression occurs primarily as a reaction to a social stimulus, often in an attempt to defend oneself from a perceived threat. Reactive aggression can result from associated feelings of frustration and anger (Berkowitz, 1989). Proactive or instrumental aggression has been characterized as controlled, deliberate, and goal-driven aggressive behavior (Dodge & Coie, 1987).…”
Section: Reactive Vs Proactive Aggressionmentioning
confidence: 99%